(untitled) (The Journal of Academic Development, 2025)
This paper explores two main ideas: first, that Kautilya was the first political economist, and second, that the study of political economy began long before Adam Smith. By examining The Arthashastra (written around 375 B.C.), we find evidence of rational decision-making, self-interest, and market activities similar to those in a traditional economy. A careful analysis shows that Kautilya’s work is just as systematic in studying political economy as Smith’s The Wealth of Nations. Since economics focuses on policies and strategies to build a nation’s wealth, the Arthashastra, meaning "The Science of Wealth," can be seen as the first detailed guide on political economy. Understanding Kautilya’s ideas helps us trace the true beginnings and development of economic thought. Looking at these historical ideas also helps us better understand modern economic theories and methods.